La responsabilité contractuelle du promoteur - Demers, Robert (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
When a promoter contracts in the name of a corporation to be formed, the question arises of knowing who will be liable on the contract. Whether the promoter of the corporation can be sought out for inexecution of the contract remains a vexed question since the famous Kelner v Baxter rules established over a century ago. In Quebec law, such rules are admitted by provincial jurisprudence but recent cases suggest alternative recourses to bind either parties. These are examined in this commentary.